2011
DOI: 10.1111/j.1600-0501.2011.02165.x
|View full text |Cite
|
Sign up to set email alerts
|

Torque removal evaluation of prosthetic screws after tightening and loosening cycles: an in vitro study

Abstract: Removal torque values tended to decrease as the number of insertion/removal cycles increased, for both groups. Comparisons of the slopes and the intercepts between groups showed no statistical difference. There was no significant difference between the mean values of last five cycles and the 11th cycle. Within the limitations of this in vitro study, it was concluded that (1) repeated insertion/removal cycles promoted gradual reduction in removal torque of screws, (2) replacing the screw with a new one after 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 24 publications
(37 reference statements)
2
24
0
3
Order By: Relevance
“…These results are similar to those obtained by Weiss et al10 in 2000 and Cardoso et al11 in 2012, who also found an inverse relationship between the tightening/loosening force and the number of cycles. However, this relationship is not true for the ball/O-ring group, which showed an increase of retention between the first and second year cycles.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are similar to those obtained by Weiss et al10 in 2000 and Cardoso et al11 in 2012, who also found an inverse relationship between the tightening/loosening force and the number of cycles. However, this relationship is not true for the ball/O-ring group, which showed an increase of retention between the first and second year cycles.…”
Section: Discussionsupporting
confidence: 92%
“…In 2012, Cardoso et al11 found no evidences that the replacing of a prosthetic screw procedure alone increases the resistance to loosening, perhaps because a modification had already occurred, possibly due to wear of the internal threads of the implant. Apparently, it is more important to restrict the number of removals than to replace the screw when inserting the definitive restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Cardoso et al12 concluded that screw loosening may pass over 20% with repeated tightening and removing cycles. Consequently detorque data may change with repetations.…”
Section: Discussionmentioning
confidence: 99%
“…As Siamos et al demonstrated, retightening could reduce torque loss by 17%‐19%. However, in most studies, the preload was believed to keep decreasing with the repeated tightening of the screw . Cardoso et al found that the removal torque value continues decreasing with the same tightening torque along the cyclic tightening and loosening of the abutment screw.…”
Section: The Mechanism Of the Abutment Screw Looseningmentioning
confidence: 99%